2008
DOI: 10.1093/eurheartj/ehn060
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor protein levels and gene expression in peripheral monocytes after stenting: a randomized comparative study of sirolimus: eluting and bare metal stents

Abstract: SES, in comparison with BMS, results in lower VEGF protein levels and gene expression in peripheral monocytes. The latter shows a positive relationship with in-stent late-luminal loss, suggesting an essential role in the reduced in-stent restenosis seen in SES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Also, drug eluting stent apposition produced a negative effect in the VEGF average changes after PCI evidencing a delay to reach control values to 1-year, which was not observed for bare metal stents. Decreases in VEGF levels were also reported on non-ACS patients treated either with statins [22] or with sirolimus eluting stent 1-month after apposition, but not in patients with bare metal stents [19]. By treating stenosis the ischemic trigger of angiogenesis is reduced [25] and this might be explained by the increase of VEGF levels [26].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Also, drug eluting stent apposition produced a negative effect in the VEGF average changes after PCI evidencing a delay to reach control values to 1-year, which was not observed for bare metal stents. Decreases in VEGF levels were also reported on non-ACS patients treated either with statins [22] or with sirolimus eluting stent 1-month after apposition, but not in patients with bare metal stents [19]. By treating stenosis the ischemic trigger of angiogenesis is reduced [25] and this might be explained by the increase of VEGF levels [26].…”
Section: Discussionmentioning
confidence: 96%
“…These studies have also evidenced the importance of the time gap of patient's evaluation on VEGF assessment. To our knowledge few studies have examined VEGF levels in CAD patients longitudinally after PCI [1719]. None of previous studies reported on changes over 1-year period after stent apposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapamycin reduces VEGF expression in both tumor and normal cells [12,14,27,28]. Therefore, we measured VEGF levels in RPE-cells treated with rapamycin.…”
Section: Vegf-expression In Rpe Cells Treated With Rapamycinmentioning
confidence: 99%
“…Given that the present study focused on patients clinically presented with CCS and DES implantation, we hypothesized that the differences in study population, implanted stents and duration of follow-up might account for the inconsistent findings. Moreover, experimental data has suggested different modes of monocyte trafficking between acute and chronic inflammation and the inflammatory response of monocytes varies in relation to type of stents ( 31 , 32 ). Therefore, the present study might provide preliminary evidence for the associations between HDL-related inflammatory indices and the risk of ISR in patients with CCS undergoing DES stenting.…”
Section: Discussionmentioning
confidence: 99%